2020
DOI: 10.21608/edj.2020.34925.1167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enamel Pre-treatment with Silver Diamine Fluoride versus Nano Silver Fluoride on the Microleakage of Fissure Sealant: in vitro study.

Abstract: Many studies in literature showed the effectiveness of silver diamine fluoride (SDF) and Nano silver fluoride (NSF) as preventive agents. However, there is little evidence regarding the retention properties of fissure sealant (FS) when applied on a surface previously treated with these preventive agents. Objective: To evaluate and compare the effect of fissure pre-treatment with SDF versus NSF on the microleakage of FS in permanent teeth. Methods: This experimental in vitro study was performed on 45 extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…They reported that a tooth surface treated with silver diamine fluoride before the application of fissure sealants decreases the microleakage of the pit and fissure sealant, but the results did not score a significant difference. This also agreed with Elhabashy and El Tekeya (34).…”
supporting
confidence: 89%
“…They reported that a tooth surface treated with silver diamine fluoride before the application of fissure sealants decreases the microleakage of the pit and fissure sealant, but the results did not score a significant difference. This also agreed with Elhabashy and El Tekeya (34).…”
supporting
confidence: 89%
“…(18,31) In the present study, Fluoridated Self-assembling peptide (Curodont TM Repair Fluoride Plus) revealed a larger zone of inhibition 21 (18)(19)(20)(21)(22) against Strep. Mutans compared to Nano silver fluoride 9 (8)(9) and Enamelast sodium fluoride varnish. Enamelast sodium fluoride varnish did not reveal any zones of inhibition, indicating no antimicrobial activity against Strep.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Although, The addition of silver ions produces a synergistic antimicrobial effect with the fluoride, silver precipitation produces dark black staining of the carious lesion, so its clinical use in the aesthetic region is discouraged. (8,9) . This leads to the development of Nano-silver fluoride (NSF) as a trial to overcome the aesthetic adverse effect of SDF using Nano-sized silver particles (AgNPs).…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmanın sonucunda NGF ve GDF'nin bağlantıyı olumsuz etkilemediği bildirilmiştir. 68 ■ Uygulaması basit, noninvaziv ve ucuzdur. 60 Tirupathi ve ark.…”
Section: Ngf'nin Uygulama Protokolü Ve Avantajlariunclassified